Microfluidic Processing of Ligand‐Engineered NiO Nanoparticles for Low‐Temperature Hole‐Transporting Layers in Perovskite Solar Cells. Issue 8 (28th June 2021) - Michalska, Monika; Surmiak, Maciej Adam; Maasoumi, Fatemeh; Senevirathna, Dimuthu C.; Chantler, Paul; Li, Hanchen; Li, Bin; Zhang, Tian; Lin, Xionfeng; Deng, Hao; Chandrasekaran, Naresh; Peiris, T. A. Nirmal; et al.
Abstract : Nickel oxide (NiO) is used as a hole‐transporting layer (HTL) in perovskite solar cells (PSCs) because of its high optical transmittance, intrinsic p‐type doping, and suitable valence band energy level. However, fabricating high‐quality NiO films typically requires high‐temperature annealing, which limits their applicability for low‐temperature, printable PSCs. Herein, the need for such postprocessing steps is circumvented by coupling 4‐hydroxybenzoic acid (HBA) or trimethyloxonium tetrafluoroborate (Me3 OBF4 ) ligand‐modified NiO nanoparticles (NPs) with a Tesla‐valve microfluidic mixer to deposit high‐quality NiO films at a temperature <150 °C. The NP dispersions and the resulting thin films are thoroughly characterized using a combination of optical, structural, thermal, chemical, and electrical methods. While the optical and structural properties of the ligand‐exchanged NiO NPs remain comparable with those possessing the native long‐chained aliphatic ligands, the ligand‐modified NiO thin films exhibit dramatic reductions in surface energy and an increase in hole mobilities. These are correlated with concomitant and significant enhancements in performance and stability factors of PSCs when the ligand‐modified NiO NPs are used as HTL layers within p−i−n device architectures. Abstract : Nickel oxide serves as an inexpensive and stable charge‐transporting layer for perovskite solar cells (PSCs). However, its high‐temperature processing limits its applicability to low‐temperature‐processed devices. Herein, ligand‐modified NiO nanoparticles are shown to permit low‐temperature (140 °C) processing into high‐quality thin films using a Tesla‐valve microfluidic mixer, which are suitable for developing stable and efficient PSCs.